Cognitive Training among Cognitively Impaired Older Adults: A Feasibility Study Assessing the Potential Improvement in Balance - Smith-Ray, Renae L.; Irmiter, Cheryl; Boulter, Kristin (Frontiers in Public Health, 2016)
Background: Emerging literature suggests that mobility and cognition are linked. Epidemiological data support a negative association between cognition and falls among cognitively intact older adults. A small number of intervention studies found that regimented cognitive training (CT) improves mobility among this population, suggesting that CT may be an under-explored approach toward reducing falls. To date, no studies have examined the impact of CT on balance among those who are cognitively impaired. The purpose of this study was to assess the feasibility of implementing a CT program among cognitively impaired older adults and examine whether there are potential improvements in balance following CT. Method: A single group repeated measures design was used to identify change in balance, depressive symptoms, and global cognition. A mixed method approach was employed to evaluate the feasibility of a CT intervention among a cohort of cognitively impaired older adults. CT was delivered in a group 2 days/week over 10 weeks using an online brain exercise program, Posit Science Brain HQ (20 hours). All participants completed a one-on-one data collection interview at baseline and post-program. Results: Participants (N=20) were on average 80.5 years old and had mild to moderate cognitive impairment. Following the 10-week cognitive training intervention, mean scores on 4 of the 5 balance measures improved among CT participants. Although none of the balance improvements reached significance, these findings are promising given the small sample size. Depressive symptoms significantly improved between baseline and 10 weeks (p=0.021). Mean global cognition also improved across the study period, but neither of these improvements were statistically significant. Based on participant responses, the CT program was feasible for this population. Conclusion: This study provides support for the feasibility of implementing a CT program among cognitively-impaired older adults in an adult day setting. Our findings also add to emerging literature that CT may be a novel and innovative approach to fall prevention among older adults.